Measurement of the B s 0-B - s 0 oscillation frequency δm s in B s 0→D s -(3)π decays - Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; Alves, A; et al. (2012)
The B s 0-B - s 0 oscillation frequency δm s is measured with 36 pb -1 of data collected in pp collisions at s=7TeV by the LHCb experiment at the Large Hadron Collider. A total of 1381 B s 0→D s -π+ and B s 0→D s -π +π -π + signal decays are reconstructed, with average decay time resolutions of 44 fs and 36 fs, respectively. An oscillation signal with a statistical significance of 4.6σ is observed. The measured oscillation frequency is δm s=17.63±0.11(stat)±0.02(syst)ps -1. © 2012 CERN.